KONSEP MESIANIK DALAM YESAYA 9:5-6 RELEVANSINYA DENGAN KEPEMIMPINAN BANGSA INDONESIA DI ERA PANDEMI COVID-19 - Ganefosius Pangandaheng (STT BIBLIKA JAKARTA, 2022)
Understanding of the Old Testament about the King and Institution of Kingdom there is a Messianic understanding. Key of Kingdom Mesianist is kindness of God which becomes part of Messiah, when he was elected as a ruler to organize the lives of God. That is the basic make God peace possible can be realized in life of the people ant the nation. Peace has a meaning which is correlated with life political, socio-economic and religious. The dimenssion of peace can mean that Messianic leader will rule with justice and righteousness. Therefore people who are marginalized, poor, weak and the oppressed get the right and decent life.